Implementation of Problem Based Micro Teaching in Improving PAI Teaching Abilities at Al Irsyad Cipanas Vocational School - Euis Latipah; Ai Atikah; Siti Soleha (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
The rapid advancement of technology and curriculum changes require prospective Islamic Religious Education (PAI) teachers to possess adaptive teaching skills and effective problem-solving abilities. This study aims to analyze the implementation of micro teaching based on Problem Based Learning (PBL) in improving the teaching competence of prospective PAI teachers at SMK Al Irsyad Cipanas. The research employed a qualitative approach with a case study method. Data were collected through observation, tests, interviews, and documentation. The findings revealed that the application of micro teaching integrated with PBL significantly improved participants' mastery of teaching materials, classroom management, learning strategy implementation, critical thinking skills, and collaboration abilities. Most prospective teachers provided positive feedback on this model, as they felt more confident and creative in addressing learning challenges. This study contributes to the development of a more contextual and practical teacher training model aligned with the demands of the Merdeka Belajar Curriculum. It is recommended that micro teaching based on PBL be widely integrated into teacher education programs, with improvements in training duration, supporting facilities, and the variety of learning materials tailored to real classroom needs.